Modern Corporate Governance Technologies are the Basis for the Development of the Organization's Economy - Vohobov Hikmatillo Ma'mirjon o'g'li (Zien Journals, 2022)
In this article, modern corporate govenance, its importance aspects and economic by stimulating management information on ways to achieve efficiency
Keywords: corporate govenance; technology; efficiency; investment